Pengaruh Ukuran Perusahaan dan Pengungkapan CSR Terhadap Nilai Perusahaan dengan GCG Sebagai Variabel Pemoderasi - Lestari, Nita Surya; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 23 No 2 (2018), 2018)
Companies need to pay attention to factors that may affect the fluctuation of corporate value. This study aims to determine the effect of firm size and disclosure of Corporate Social Responsibility (CSR) to corporate value with Good Corporate Governance (GCG) as moderating variable. This research was conducted at a public listed company listed on the Indonesia Stock Exchange and followed the Corporate Governance Perception Index program successively from 2011-2015. The number of population in this research is 539 companies and samples taken as many as 6 companies, with probability sampling method. Data collection was done by non participant observation technique. Analytical techniques used are multiple linear regression and Moderated Regression Analysis. The results of the analysis show that firm size has a positive effect on corporate value, Corporate Social Responsibility (CSR) disclosure has a positive effect on company value, GCG strengthens the firm size and disclosure of Corporate Social Responsibility (CSR) to company value. Keywords: company value, company size, CSR, GCG